The Role of Brand Trust in Mediating the Effect of Social Media Marketing on Brand Loyalty at Falala Chocolate Customers in Denpasar - Dewi, Ni Ketut Meicintia; Wardana, I Made (Universitas Warmadewa, 2023)
Consumption of chocolate in Indonesia continues to increase every year, this can be an opportunity for businessmen to open a business with the main product of chocolate. Falala Chocolate Bali takes advantage of this opportunity by selling and marketing unique and attractive artisan chocolate products. This study aims to analyze the role of brand trust in mediating the effect of social media marketing on brand loyalty. This study was conducted at Falala Chocolate in Denpasar City, with a sample of 100 people who were determined by purposive sampling. Data was collected using a survey approach, and the study instrument was a questionnaire measured by a Likert scale. The data were analyzed using path analysis. The results of this study indicate that all hypotheses are accepted. Social media marketing has a positive and significant effect on brand loyalty, social media marketing has a positive and significant effect on brand trust, brand trust has a positive and significant effect on brand loyalty, and brand trust has a significant role in mediating the influence of social media marketing on brand loyalty.